2014
DOI: 10.9790/2380-07231318
|View full text |Cite
|
Sign up to set email alerts
|

Apply traditional and molecular protocols for the detection of carrier state of visceral leishmaniasis in black Bengal goat

Abstract: Visceral leishmaniasis (VL) is the second largest parasitic killer of human in the world after malaria which is responsible for an estimated 500,000 new cases of VL in each year with 8-10% mortality. The parasite is transmissible to humans and animals by the bite of phlebotomine sand fly. The clinical manifestations are highly diverse, humans and dogs are naturally infected, and the diseases are associated with several risk factors, yet to understand. The aims of this study were to apply traditional and molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…To determine whether the same parasite clone is present, the Leishmania ITS1 DNA sequences of VL and CL patients in this study area should be compared to that extracted from infected dogs, rodents, sand flies and livestock. Several previous studies in Leishmania endemic regions around the world have reported Leishmania infection in livestock, consistent with present study findings, although these studies differ in terms of sample size, diagnostic method applied, types of samples, presence of heterogeneous parasite populations and immune responses to the Leishmania parasite [ 12 14 , 16 , 26 ]. In the present study, some samples were positive by both molecular and serological methods (51/181; 28.2%), while others were positive by only one method.…”
Section: Discussionsupporting
confidence: 91%
“…To determine whether the same parasite clone is present, the Leishmania ITS1 DNA sequences of VL and CL patients in this study area should be compared to that extracted from infected dogs, rodents, sand flies and livestock. Several previous studies in Leishmania endemic regions around the world have reported Leishmania infection in livestock, consistent with present study findings, although these studies differ in terms of sample size, diagnostic method applied, types of samples, presence of heterogeneous parasite populations and immune responses to the Leishmania parasite [ 12 14 , 16 , 26 ]. In the present study, some samples were positive by both molecular and serological methods (51/181; 28.2%), while others were positive by only one method.…”
Section: Discussionsupporting
confidence: 91%
“…The important zoonotic diseases only noted in the hospital data sheet during passive surveillance was anthrax. Brucellosis (Dey et al, 2013) and Tuberculosis in dairy cattle , Leishmaniasis in goats (Labony et al, 2014) and canids and avian influenza in chickens (Bari et al, 2009) and ducks were endemic in Bangladesh and extremely zoonotic, these diseases were not included in the hospital data sheet. The passive surveillance protocols were, therefore, unable to analyze frequency distribution of the existing zoonotic diseases of livestock and poultry in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…Portion of lungs were collected aseptically, snap frozen and used for bacterial DNA extraction and detection of TB by using multiplex and uniplex PCR. In brief, 2 gm frozen tissues were crushed in liquid nitrogen and extracted bacterial DNA using conventional method [9]. The quality and quantity of the extracted DNA was measured by using agarose gel electrophoresis and spectrophotometry (SpectronicR Genetics TM New York, USA) (A260/A280).…”
Section: Pcr Detection Of Mycobacterium Spp 231 Extraction Of Bactmentioning
confidence: 99%